EVALUASI PENGGUNAAN SOSIAL MEDIA FACEBOOK DAN WHATSAPP TERHADAP LAYANAN INFORMASI AKADEMIK - Cindi Wulandari; Elmayati Elmayati; Reka Putria Wati (LPPM UNIVERSITAS BINA INSAN, 2020)
Abstract The problem in this study was, there where no researchs about satisfy level of Facebook and WhatsApp social media user for academic service. This study was refers to SERVQUAL (Service Quality) method in descriptive qualitative by measuring 5 indicators they were tangible, reability, responsivenes, assurance, and emphaty. This study show that there was an effect between five variables and Facebook and WhatsApp social media user to ward Academic Service Satisfy at Economic and Business Faculty of Bina Insan University Lubuklinggau. The conclusion of this study show that five variables tangible, reability, responsivenes, assurance, and emphaty was valid and reliable. By measuring Facebook and WhatsApp social media user satisfy level. It expected Facebook and WhatsApp social media will be one of connection in developing teaching, research, and community service process between lectures, teachers, and students. Keywords : facebook and WhatsApp social media, SERVGQUAL (Service Quality) method